2021
DOI: 10.3390/dj9050047
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards Telemonitoring in Orthodontists and Orthodontic Patients

Abstract: The purpose of this study was to analyze the attitude of dentists and patients towards the use of Dental MonitoringTM (DM), an orthodontic telemonitoring software. Thus, two different specially prepared specific questionnaires were administered to 80 dentists (40 were general dentists and 40 orthodontists) and 80 orthodontic patients. All dentists judged positively telemonitoring, as 96.25% of them considered telemonitoring indicative of high tech and high-quality treatment; 100% considered it a way to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…Recent studies have found that tele-monitoring and remote monitoring are positive approaches to evaluate the orthodontic health status of the patient in this pandemic era. 15,16 The use of smartphones and digital technology can be useful in evaluating the progression of the treatment and improving the patient's cooperation. 17 Due to the current pandemic, 63% of the patients could not visit their orthodontist for the last 3-6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that tele-monitoring and remote monitoring are positive approaches to evaluate the orthodontic health status of the patient in this pandemic era. 15,16 The use of smartphones and digital technology can be useful in evaluating the progression of the treatment and improving the patient's cooperation. 17 Due to the current pandemic, 63% of the patients could not visit their orthodontist for the last 3-6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Debonding incidents were mostly caused by patientadmitted non-compliance during eating and material damage was rare. Interesting aspect of this study is that all orthodontic patients` intraoral situation was monitored remotely with tele-Health solution -Dental Monitoring, which is judged positively with orthodontists Dalessandri et al 2021 [73] Small differences in material properties had no clinically relevant impact on the distalizers performance. Implication of these findings might suggest wider possibility of suitable materials -dedicated dental resins.…”
Section: Discussionmentioning
confidence: 99%
“…Resin infiltration is considered useful in terms of both reducing the WSL area and to increasing its esthetic appearance [38]. Innovative systems such as telemonitoring and web-based smartphone apps, reducing plaque accumulation and ameliorating overall oral hygiene, help to reduce a factor favorable for WSL onset [39,40].…”
Section: Discussionmentioning
confidence: 99%